Análisis de resonancia por efecto de onda larga en la dársena de Puerto Moín - Alfaro Corrales, Luis Felipe (2017)
UCR::Vicerrectoría de Docencia::Ingeniería::Facultad de Ingeniería::Escuela de Ingeniería Civil